Growing makhana for high income - Khadatkar, Abhijit; Gupta, V K (Indian Horticulture, 2023)
Makhana (Euryle ferox Salisb.) is normally grown in stagnant water bodies like ponds, low depressions, lakes, etc. In the traditional system, 10% of the seeds germinate from the leftover seed of previous crop in the same pond. The harvesting or collection of scatteredMakhana seeds from the bottom surface of the pond is very tedious and painful activity, which involves a lot of drudgery. There are a number of constraints that limit the cultivation of makhana.